Occurrence of marine fungi from the Straits of Malacca, Malaysia, with first record of Mauritiana rhizhoporae - Zainuddin, Nazura; Sarah Sharuddin, Siti; Aisyah Alias, Siti (Malaysian Journal of Science, 2008)
The inventory of marine fungi along the Straits of Malacca was carried out in July, 2004 and December, 2007. Three locations were investigated for their marine fungal diversity: Lalang Island, Jarak Island and Rumbia Island. Samples collected from these islands were submerged wood and driftwood entrapped in between rocks, embedded in sand and washed ashore along the coastal areas. A total of 51 species of marine fungi were recorded from 274 samples collected and their frequency of occurrence is discussed. Mauritiana rhizophorae is reported as the first record in Malaysia.